A Review of Voltage and Current Signature Diagnosis in Industrial Drives - K. Vinoth Kumar (Institute of Advanced Engineering and Science, 2011)
This paper presents the review of identify the different types of faults in the induction motor during online condition by using current and voltage signature analysis. Special attention is focused on the effect of both space distribution of rotor breakage and rotor dis-symmetry on the mechanism of generation of diagnosis signatures with the consideration of voltage supply unbalance and speed ripples. A comparison is made between the voltage signature analysis and current signature analysis. Keywords: Fault diagnosis, Induction motor, rotor breakage, MCSA, Motor voltage signature analysis (MVSA).DOI: http://dx.doi.org/10.11591/ijpeds.v1i1.64